دور المجتمع المدني في التخفيف من النزاعات الزوجية - ديبوش, يونس (جامعة الوادي - University of Eloued, 2022)
تفاقم النزاعات الزوجية بشكل يبعث على القلق من حيث تنوع أساليبها من جهة، ومن حيث حدتها وآثارها من جهة أخرى، وهذه المقالة تركز على دور المجتمع المدني في التقليل من تلك النزاعات التي تؤدي إلى تداعي أركان المجتمع وتهدد بزوال خليته الأولى وهي الأسرة. المجتمع المدني يضم أطرافا متعددة وفاعلة يمكن الانتفاع بها في التصدي لظاهرة النزاعات الزوجية وتلافي اللجوء إلى المحاكم. Abstract: The marital conflicts are increasing in an alarming way concerning their various ways from one hand and their intensity and negative effects on the other . This article focuses on the role of civil society in diminishing those conflicts which lead to weakening the society angles and threaten lay disappearance the family. The civil society comprises different active members who may be useful to face the phenomenon of marital conflicts and to avoid referring to courts.
The role of civil society in alleviating marital conflicts
مقال
Keywords: النزاع ، النزاعات، التخفيف ، المجتمع; family society conflits